The influence of body roll on hand path in freestyle swimming: A computer simulation study - Hay, J. G.; Liu, Q.; Andrews, J. G. (Journal of Applied Biomechanics, 1993)
The "S-shaped" path of a crawl stroke pull has been promoted as worthy of development and even exaggeration so that lift forces will be increased. This study showed that the opposite is true. The curved path of a crawl stroke hand movement is due mainly to body roll. It was shown that when the arm was simulated to move directly backward with respect to a swimmer's reference frame, the path of the hand in the external reference frame was more curved than in actual swimming. This means that swimmers manipulate their movements to somewhat straighten the path of the hand movements. Rather than swimmers adducting the arm to produce the "insweep" and then abducting to produce the "outsweep", as commonly demonstrated by coaches, swimmers actually reduce the curve by abducting in the early phase of the pull (outward rotation of the upper arm), and adducting during the latter phase of the pull. Implication: The curved path exhibited by most swimmers is not deliberate. Swimmers attempt to straighten the movement path rather than use sculling actions. This is strong indirect evidence that swimmers primarily rely on drag forces rather than lift forces.